2007
DOI: 10.1038/sj.jhh.1002164
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function in normotensive and high-normal hypertensive subjects

Abstract: To evaluate the impact of a mild increment in blood pressure level on endothelial function, we evaluated 61 healthy volunteers (24 women, 37 men, and aged 35-50 years). All subjects underwent a blood chemistry panel to exclude any metabolic abnormalities and were submitted to a Doppler ultrasound of the brachial artery to assess endothelial function. We assessed the endothelial response to reactive hyperaemia and exogenous nitric oxide administration considering an increase in systolic blood pressure (SBP) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
1
18
2
4
Order By: Relevance
“…11 More recently, Plavnik et al showed that in a healthy normotensive (SBP <140 mmHg) population aged 35-50 years, without any risk factor for atherosclerotic disease, subjects with SBP ≥115 mmHg, when compared with subjects with SBP <115 mmHg, had a significant reduction in FMD for every 10 mmHg increase in SBP. 22 In agreement with them, our study demonstrated that FMD was lower in subjects with SBP <120 mmHg than in those with >120 mmHg in the non-smoking group.…”
Section: Discussionsupporting
confidence: 79%
“…11 More recently, Plavnik et al showed that in a healthy normotensive (SBP <140 mmHg) population aged 35-50 years, without any risk factor for atherosclerotic disease, subjects with SBP ≥115 mmHg, when compared with subjects with SBP <115 mmHg, had a significant reduction in FMD for every 10 mmHg increase in SBP. 22 In agreement with them, our study demonstrated that FMD was lower in subjects with SBP <120 mmHg than in those with >120 mmHg in the non-smoking group.…”
Section: Discussionsupporting
confidence: 79%
“…4 As with LVH, a defect EDV has also been shown to predict future cardiovascular events. 5,6 Previous studies have shown LVH to be related to an impaired EDV in hypertensive subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Plavnik et al [12] have analyzed the nitrate-mediated endothelium-dependent and -independent vasodilation response (FMD) in 33 normotensive subjects compared to 28 normal-high blood pressure subjects with age and BMI similar to those of the present study and the authors have demonstrated a flow-mediated vasodilation response about 30% lower in the first group, suggesting endothelial dysfunction at prehypertension levels. Nevertheless, there subjects were mainly males, and race and sedentary lifestyle were not study variables.…”
Section: Discussionmentioning
confidence: 88%
“…[9,10] Nevertheless, data on the influence of clinical and epidemiological profile of prehypertensive subjects on endothelial function is lacking and little is known about the relationship between intermediate cardiovascular phenotypes and race differences. Pulse wave velocity seems to be greater in Africans than in Europeans.[11] Plavnik et al [12], when comparing the endothelial function of prehypertensive and normotensive subjects, have showed no impact of body weight on FMD in either group.This study aimed at evaluating the endothelial function of prehypertensive subjects by FMD and investigating the association of demographic, anthropometric and clinical characteristics with endothelial dysfunction. …”
mentioning
confidence: 99%